2020
DOI: 10.1128/msphere.01102-20
|View full text |Cite
|
Sign up to set email alerts
|

Corrected and Republished from: A Nonfunctional Opsonic Antibody Response Frequently Occurs after Pneumococcal Pneumonia and Is Associated with Invasive Disease

Abstract: Numerous reports on the dynamics of antipneumococcal immunity in relation to immunization with pneumococcal vaccines and on the prevalence of naturally acquired immunity in various populations have been published. In contrast, studies on the dynamics of the humoral immune response triggered by pneumococcal infection are scarce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In contrast to its opsonic counterpart, a non-opsonic antibody binds to its antigen without contributing to eradicating the pathogen by phagocytosis (Bahnan et al, 2021; Bläckberg et al, 2021; Forthal, 2015). Recently, Bläckberg et al reported that patients suffering from an invasive Streptococcus dysgalactiae infection failed to develop protective opsonic antibodies (Bläckberg et al, 2021), and Uddén et al found that the generation of non-opsonic antibody responses was correlated to the invasive nature of the Streptococcus pneumoniae infection (Uddén et al, 2020). However, it is unknown to what extent this occurs for S. pyogenes infections and how important the nature of the infection, and in particular invasive disease, is in developing opsonizing antibodies to S. pyogenes .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to its opsonic counterpart, a non-opsonic antibody binds to its antigen without contributing to eradicating the pathogen by phagocytosis (Bahnan et al, 2021; Bläckberg et al, 2021; Forthal, 2015). Recently, Bläckberg et al reported that patients suffering from an invasive Streptococcus dysgalactiae infection failed to develop protective opsonic antibodies (Bläckberg et al, 2021), and Uddén et al found that the generation of non-opsonic antibody responses was correlated to the invasive nature of the Streptococcus pneumoniae infection (Uddén et al, 2020). However, it is unknown to what extent this occurs for S. pyogenes infections and how important the nature of the infection, and in particular invasive disease, is in developing opsonizing antibodies to S. pyogenes .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to its opsonic counterpart, a nonopsonic antibody binds to its antigen without contributing to eradicating the pathogen by phagocytosis ( 16 , 21 , 22 ). Recently, Bläckberg et al reported that patients suffering from an invasive Streptococcus dysgalactiae infection failed to develop protective opsonic antibodies ( 22 ), and Uddén et al found that the generation of nonopsonic antibody responses was correlated with the invasive nature of the Streptococcus pneumoniae infection ( 23 ). However, it is unknown to what extent this occurs for S. pyogenes infections and how important the nature of the infection, and in particular invasive disease, is in developing opsonizing antibodies to S. pyogenes .…”
Section: Introductionmentioning
confidence: 99%